Iron Deficiency Prior to Discharge in Very Low Birth Weight Infants: Screening with Reticulocyte Hemoglobin Content - Kennady, Geetika; Afridi, Faraz; Neumann, Dana; Amendolia, Barbara; Kilic, Nicole; Bhat, Vishwanath; Bhandari, Vineet; Aghai, Zubair H. (American Journal of Perinatology, 2023)
Objective This study aimed to assess the iron status prior to discharge in very low birth weight (VLBW) infants utilizing reticulocyte hemoglobin content (CHr) and evaluate the impact of delayed cord clamping (DCC) on iron status.Study Design This is a retrospective analysis of VLBW infants from two tertiary level of care Neonatal Intensive Care Units. The primary outcome was the proportion of VLBW infants with low CHr (<29 pg) prior to discharge. Hematologic parameters were also compared between infants who received or did not receive DCC. Infants with a positive newborn screen for hemoglobin Bart's were excluded.Results Among the 315 infants included, 99 infants (31.4%) had low CHr prior to discharge. The median (interquartile range) CHr prior to discharge was 30.8 pg (28.4–39 pg). DCC was performed in 46.7% of infants. Hemoglobin at birth, discharge, and CHr prior to discharge were higher and the need for blood transfusion and the number of infants with low CHr prior to discharge were lower in the DCC group.Conclusion Approximately 31.4% of VLBW infants had low CHr near the time of discharge suggesting they were iron deficient. DCC improved hematological parameters prior to discharge in VLBW infants. CHr content can be used to guide iron supplementation in VLBW infants to potentially improve their iron status and long-term neurocognitive outcomes.Key Points
Keywords: reticulocyte hemoglobin content; neonate; preterm; anemia; iron deficiency